Formation of legal culture of Ukrainian people in the Ukrainian philosophy - N. P. Boyko (Granì, 2016)
This study, which deals with the author, is the manifestation of scientific and methodological criteria on which formed Ukrainian legal culture. The methodological base regarding the study of philosophy, legal political ideological and theoretical positions were the subject of modern scientific research in the field of philosophy, political science and cultural studies that formed the scientific categories and methods of philosophical and legal analysis. Categorical principle that was the basis for this study is historical - cultural analysis, which specifies the topic of spiritual research side, maturing Ukrainian culture right in the historic plane and using philosophical and methodological apparatus. It was drawn to the factor that the members of the Cyril and Methodius laid the principles of legal culture in Ukraine. Indicated that they perceived critically civilization and its pryvady who poured on people’s minds and changed their culture. The forms of social life are the basic features of social and collective coexistence, rationality in household and personal culture of Ukrainian as the root principles of democratic governance, with the right people had a higher law than the decisions of the individual leader, in this world, the person is a civil person who is the political basis for the rule of law. Ukrainian Legal awareness is a hot topic of modern philosophical studies in crisis social and political phenomena.